1999
DOI: 10.1097/00000542-199911000-00040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia–Reoxygenation on Microvascular Endothelial Function in the Rat Hippocampal Slice 

Abstract: Even brief periods of hypoxia may cause endothelial dysfunction in intraparenchymal cerebral arterioles. This does not seem to be related to a deficiency of the nitric oxide substrate, L-arginine. Endothelial dysfunction and impaired endothelium-dependent dilation of microvessels may decrease oxygen delivery and increase neuronal injury during cerebral hypoxia-reoxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
4
0
3
Order By: Relevance
“…Cerebral hypoxia and ischemia can lead to injury of both parenchymal and vascular cells. The resultant cerebrovascular endothelial injury is manifested as impairments in autoregulation and vascular reactivity (Christopherson et al, 1993; Staunton et al, 1999), reduced expression of tight junction proteins (Fischer et al, 2002; Petty and Lo, 2002; Witt et al, 2003), increases in blood-brain barrier permeability (Petty and Lo, 2002; Witt et al, 2003), hypoperfusion, microvascular hemorrhage (Wang and Lo, 2003), and frank endothelial cell death. Moreover, endothelial cell ‘activation’ after hypoxia or ischemia is reflected by the production of proinflammatory mediators, adhesion molecule expression, and leukocyte and platelet adherence to endothelium with attendant microvascular plugging (del Zoppo and Mabuchi, 2003), all of which can impact significantly on neuronal injury and overall outcome after cerebral hypoxic and/or ischemic insults.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral hypoxia and ischemia can lead to injury of both parenchymal and vascular cells. The resultant cerebrovascular endothelial injury is manifested as impairments in autoregulation and vascular reactivity (Christopherson et al, 1993; Staunton et al, 1999), reduced expression of tight junction proteins (Fischer et al, 2002; Petty and Lo, 2002; Witt et al, 2003), increases in blood-brain barrier permeability (Petty and Lo, 2002; Witt et al, 2003), hypoperfusion, microvascular hemorrhage (Wang and Lo, 2003), and frank endothelial cell death. Moreover, endothelial cell ‘activation’ after hypoxia or ischemia is reflected by the production of proinflammatory mediators, adhesion molecule expression, and leukocyte and platelet adherence to endothelium with attendant microvascular plugging (del Zoppo and Mabuchi, 2003), all of which can impact significantly on neuronal injury and overall outcome after cerebral hypoxic and/or ischemic insults.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings are also consistent with the concept that a period of relative hyperoxia may contribute to hypoxia-induced neuronal injury. Similarly, Stauton and coworkers8 have shown that hypoxemia–reoxygenation causes endothelial dysfunction in intraparenchymal cerebral arterioles by impairing endothelium-dependent dilation of microvessels, which in turn may decrease oxygen delivery and increase neuronal injury. The use of protein S100 beta release as a marker of cerebral injury remains controversial inasmuch as it has been shown to be affected by potential contamination from sources such as bypass suckers and mediastinal fat 21.…”
Section: Discussionmentioning
confidence: 88%
“…Hypoxia and reoxygenation have also emerged in recent years as very important mechanisms of cerebral and hepatic injury 7,8. Matheis and associates,9 in a small, observational study, demonstrated that uncontrolled hyperoxic reoxygenation on CPB for surgical correction of congenital heart defects was associated with higher S100 levels in cyanotic infants as compared with acyanotic patients undergoing comparable operations, while hepatic reoxygenation injury has been demonstrated in experimental animal models 10…”
mentioning
confidence: 99%
“…This tendency is highlighted in several tissues, such as skeletal muscle, heart, lung and brain. [79]- [82] The combined effects of IR and inflammation on arteriolar vasomotricity are well documented. The increase in the contractile response of the pulmonary and mesenteric microcirculation after cardiac surgery predisposes the patient to the development of pulmonary shunt or mesenteric ischemia, particularly during the administration of vasopressive drugs in the postextracorporeal circulation.…”
Section: At the Arteriolar Levelmentioning
confidence: 99%